The Effectiveness of Problem-Based Learning in Improving Fourth-Grade Students’ Creative Thinking in Science - Toruan, Christin Natalia Lumban; Thesalonika, Emelda; Purba, Natalina (International Journal of Contemporary Studies in Education, 2026)
Purpose – This study aims to examine the effect of the Problem-Based Learning (PBL) model on the creative thinking skills of fourth-grade students in Natural and Social Sciences (IPAS) at SD Negeri 091608 Sinaksak. The research was motivated by students’ low creative thinking ability due to teacher-centered instruction and limited active participation. Methodology – A pre-experimental design using a one-group pretest–posttest approach was employed. The sample consisted of 23 fourth-grade students (12 boys and 11 girls). Data were collected through pretest and posttest instruments measuring creative thinking skills. Instrument validity and reliability were tested, and data were analyzed using the N-Gain test to determine the level of improvement after the PBL intervention. Findings – The results indicate a significant improvement in students’ creative thinking skills following the implementation of PBL. The average score increased from 50.22 (pretest) to 83.86 (posttest). Initially, most students did not achieve mastery, whereas after the intervention almost all students met the learning criteria. N-Gain scores ranged from 0.56 to 1.00, indicating moderate to high improvement. These findings suggest that PBL effectively enhances creative thinking in IPAS learning. Novelty – This study provides empirical evidence of the effectiveness of PBL in improving elementary students’ creative thinking skills within the integrated IPAS subject context. Significance – The findings benefit teachers, school administrators, and curriculum developers seeking effective student-centered learning strategies to foster creativity in primary education.